A Case of Implantable Collamer Lens (ICL) with Reverse Orientation for 10 Years - Bader S. AlQahtani; Abdulaziz A. Alshamrani; Raed E. Alsulami; Jose M. Vargas (Case Reports in Ophthalmological Medicine)
Background. Implantable collamer lens (ICL) might rarely cause complications that warrant explantation. Here, we presented a case of inverted ICL that has undergone explantation after a 10-year duration. Case Presentation. A 49-year-old male with past ocular history of ICL implantation 10 years ago presented complaining of progressive decrease of visual acuity in the left eye for a long time. On examination, decreased visual acuity, anterior subcapsular cataract, and low ICL vault were noted. The anterior segment optical coherence tomography (AS OCT) showed inverted ICL. The ICL was explanted, and cataract surgery was done. Conclusion. Inverted ICL should be kept in mind as a rare cause of long-term poor visual acuity in patient with a history of ICL surgery.